Pelatihan dan Pendampingan Muhadatsah Yaumiyah Pembelajaran Bahasa Arab Kelas 8 MTs Fatah Hasyim di Pesantren Al Mardliyah - Hidayah, Bashirotul; Holik, Abd.; Masykur, Muhammad Zakki; Unsi, Baiq Tuhfatul; Ma’sum, Muhammad Asrori; Mutmainah, Lailatul; Sari, Putri Nilam (ABDIMASY: Jurnal Pengabdian Kepada Masyarakat, 2024)
The most important thing for Class 8 Students at Mts Fattah Hasyim Tambak Beras Jombang is that it is hoped that it will provide the best results for the students of Al Mardliyah Islamic Boarding School and the targets targeted by the program. The first problem is the lack of knowledge that Islamic boarding school students have regarding Arabic. The solution provided is through muhadatsah yaumiyah in learning Arabic. The approach method for implementing community service activities at the Al Mardliyah Islamic Boarding School in this PKM activity includes providing muhadtsah yaumiyah material, and practicing speaking Arabic well and correctly. The provision of Arabic language material is carried out at the beginning of learning activities and the introduction of Arabic language mufrodat. The material taught in this activity is Arabic and mufrodat yaumiyah material through writing and delivery and intensive assistance until students can speak Arabic well and correctly. Through this learning activity, it is hoped that it can solve the problems faced by grade 8 students of Mts Fattah Hasyim. This activity aims to see the activeness and skills of female students in participating in Arabic language learning (muhadtsah yaumiyah).